A System Using Implicit Feedback and Top Ranking Sentences to Help Users Find Relevant Web Documents - White, Ryen W.; Jose, Joemon M.; Ruthven, Ian (25th Annual International ACM SIGIR Conference on Research and Development in Information Retrieval (SIGIR 2002), Tampere, Finland, 2002)
We present a web search interface designed to encourage users to interact more fully with the results of a web search. Wrapping around a major commercial search engine, the system combines three main features; real-time query-biased web document summarisation, the presentation of sentences highly relevant to the searcher's query, and evidence captured from searcher interaction with the retrieval results.